1986
DOI: 10.1002/ajmg.1320240214
|View full text |Cite
|
Sign up to set email alerts
|

Role of chromosome aberrations in recurrent abortion: A study of 269 balanced translocations

Abstract: We have studied a sample of 5,445 couples in which the woman was ascertained to have had two or more spontaneous abortions: 396 from our Cytogenetics Unit (present series) and 5,049 from the literature (literature series). In approximately 5% of these couples one of the members was a carrier of a balanced translocation, either reciprocal (2/3 of cases) or Robertsonian (1/3). In 1% of the couples there were other chromosome anomalies, mostly gonosomal aneuploidies or mosaicisms. A pericentric inversion of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 50 publications
3
51
1
Order By: Relevance
“…The size of the chromosomal segment involved the frequency of the breakpoints and their positions have a vital role in reproduction. In translocations, breakpoints are nonrandom, especially in couples with Bad Obstetric History [25].The frequently involved chromosomes in the translocations in the present study were 1, 5, 7, 9, 14 & 16. The molecular characterization of the three novel translocation cases mentioned in this study was not reported in the literature involving those breakpoint regions.…”
Section: Discussionmentioning
confidence: 41%
“…The size of the chromosomal segment involved the frequency of the breakpoints and their positions have a vital role in reproduction. In translocations, breakpoints are nonrandom, especially in couples with Bad Obstetric History [25].The frequently involved chromosomes in the translocations in the present study were 1, 5, 7, 9, 14 & 16. The molecular characterization of the three novel translocation cases mentioned in this study was not reported in the literature involving those breakpoint regions.…”
Section: Discussionmentioning
confidence: 41%
“…It has been found that the relative risk of inv(9)(qh) positive couples having spontaneous abortions compared to inv(9)(qh) negative couples is not significantly increased statistically (De la Chapetla et al, 1974;Campana et aL, 1986). In the father of our proband the inverted segment was so large that the frequency of abortion might be low, The three spontaneous abortions observed in our family might have been by chance.…”
Section: Discussionmentioning
confidence: 53%
“…In the interphase diagnosis, we should be careful to use some FISH probes, such as the 16qter probes in family 1, which produce weak cross-hybridization to a few other telomeres (Ning et al 1996), although this cross-hybridization is negligible in the metaphase diagnosis. Campana et al (1986) reported that a reciprocal translocation carrier was found by conventional cytogenetics technique in 181/5445 (3.3%) of the couples who had medical histories of recurrent abortions. On the other hand, Flint et al (1995) reported that three in 99 idiopathic mentally retarded patients with normal routine karyotypes had subtelomeric chromosomal rearrangements using hypervariable DNA polymorphism analysis.…”
Section: Discussionmentioning
confidence: 99%